2002
DOI: 10.1021/ma012056z
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Phase Sequence Including Cholesteric, Smectic A, and Columnar Phases Observed in a Thermotropic LC System of Simple Rigid-Rod Helical Polysilane

Abstract: Liquid crystal phases formed by rigid-rod polymers have been studied extensively in both theoretical and experimental ways. In the initial stage of theoretical approach, it has been shown that a system of long, hard molecules can exhibit an orientationally odered nematic phase if the density is efficiently high. 1 Recently, computer simulation has played an important role in understanding the liquid crystalline behavior of systems composed of hard rod molecules and has given the first indication that the smect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 20 publications
(44 reference statements)
1
44
0
Order By: Relevance
“…Recently, a number of artificial helical polymers bearing enantiomerically pure chiral or achiral bulky functional side groups have been successfully prepared by the precisely controlled polymerization of functional monomers with well‐defined catalysts 27–35. These synthetic helical polymers exhibit many interesting characteristics, including electronic and photophysical properties,21, 36 the formation of thermotropic liquid crystals,37, 38 chiral and chirality recognition ability,39–51 and helix–helix transition 48, 52–61. Therefore, understanding the relationship between the functions and the global structures and local conformations is crucial in this field 27–35.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of artificial helical polymers bearing enantiomerically pure chiral or achiral bulky functional side groups have been successfully prepared by the precisely controlled polymerization of functional monomers with well‐defined catalysts 27–35. These synthetic helical polymers exhibit many interesting characteristics, including electronic and photophysical properties,21, 36 the formation of thermotropic liquid crystals,37, 38 chiral and chirality recognition ability,39–51 and helix–helix transition 48, 52–61. Therefore, understanding the relationship between the functions and the global structures and local conformations is crucial in this field 27–35.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The most interesting property of these materials is an ability to form layered structures in crystals and liquid crystals when the alkyl side chains reach a critical length. The layered mesophases are characterized by a closed packing of the rigid-rod main chains into layers with the molten side chains occupying a space between the layers.…”
mentioning
confidence: 99%
“…During the initial stage of these studies, the numerical experiments and computer simulations revealed that the most common LC sequence of the nematic-smecticcolumnar phases could be reproduced in the hard-rod particle model systems [1,2]. These theoretical predictions agreed well with the thermotropic LC behavior of rigidrod helical polysilanes with narrow molecular weight distributions [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 61%